The effectiveness of moisturizers in the management of burn scars following burn injury: a systematic review. (October 2015) - Klotz, Tanja; Kurmis, Rochelle; Munn, Zachary; Heath, Kathryn; Greenwood, John E
Executive summary : Background : The common mantra with which patients often leave a burns unit is "moisturize and massage". Various products have been reported for use in practice including aqueous cream BP, bees wax and herbal oil creams, silicone based creams, paraffin/petroleum/mineral oil based products and aloe vera gels. Often combined with other scar management techniques such as pressure therapy, massage and contact media, moisturizers convey active properties of their own. To date no published review on the optimal moisturizer for burn scar management has been identified via searches of recognized databases. Objectives : The objective of this review was to identify and synthesize the best available evidence on the effectiveness of moisturizer use in the management of active burn scars following burn injury. More specifically, this review focused on the following questions: Does moisturizer use have an effect on scar outcomes following burn injury, including scar formation, skin breakdown, patient acceptance and water loss? What is the optimal base composition of moisturizers used in scar management for patients who have sustained a burn injury? Inclusion criteria : Types of participants Patients of any age who have sustained a burn injury of any size, and have been admitted to a hospital or regional burn unit or burn centre for the management of their injury. Types of intervention(s)/phenomena of interest Studies evaluating moisturizer applied to healed skin following burn injury were considered for inclusion. Moisturizer may have been compared to usual care as defined by the individual study, other interventions, or a different type of moisturizer. Studies comparing moisturizer and massage compared to moisturizer alone were excluded. Types of studies This review primarily considered experimental study designs, including randomized and pseudo‐randomized controlled trials. Types of outcomes Primary outcomes for examination in this review included scar formation and skin breakdown, measured by objective tools or subjective scales. Secondary outcomes included product acceptance, patient compliance and transepidermal water loss. Search strategy : A search was conducted to identify published and unpublished studies via electronic databases. Reference lists of all papers selected for full text retrieval were then hand searched for potential additional citations. Methodological quality : Articles meeting pre‐determined eligibility criteria for the review were assessed by two independent reviewers using standardized checklists from the Joanna Briggs Institute Meta Analysis of Statistics Assessment and Review Instrument. Corresponding authors were contacted where additional information was required; however this strategy did not yield additional information that altered study eligibility status. Data extraction : Data was extracted from the included paper using the standardized data extraction tool from the Joanna Briggs Institute Meta Analysis of Statistics Assessment and Review Instrument. Data synthesis : Narrative synthesis of the included study was undertaken. Results : One study, following a randomized controlled design, was eligible for inclusion in this review. This study investigated the effect of vitamin E cream versus a base moisturizing cream on outcomes including range of motion, scar thickness, cosmetic appearance and graft size. No significant differences between groups for all reported outcomes were observed. Conclusions : Despite the common practice involving moisturizers as part of burns scar management, there is a current lack of evidence to inform optimal moisturizer choice.